Drivers and perceived constraints on Dutch dairy farms to engage in disease prevention - Jorritsma, Ruurd; Swinkels, Jantijn; Werven, Tine van; Lahaye, Nadia; Martena, Merel; Stok, Marijn (Frontiers in Veterinary Science, 2023)
Introduction While prevention is increasingly important in the dairy sector, implementation of cost-effective preventive measures is often lacking. To increase the use of these measures and consequently improve animal welfare and reduce financial losses for farmers, it is necessary to know the drivers and constraints of farmers to engage in prevention. Methods Therefore, we invited farmers to participate in an online questionnaire, which contained questions about their behavior toward either claw health or calf health. We used the theory form the Stage of Change model, COM-B, as well as the Theory of Planned Behavior to formulate our questions. We used the responses of 226 farmers in our analyses, who were equally distributed over the two groups of diseases. Results and discussion We found that 63.5% of responding farmers were in the action phase or the maintenance phase to prevent claw diseases and even more (85.4%) to prevent calf diseases. The responses also suggest that many farmers have the knowledge and skills to implement preventive measures for both claw and calf diseases. The scores for social and physical opportunities for calf diseases were significantly higher than for claw diseases and all other COM-B components were also numerically higher for calf diseases. This suggests that farmers' perception of taking preventive measures against claw diseases is more difficult than taking preventive measures against calf disease. The automation of preventive behavior scored relatively low for both groups of diseases, which suggests that farmers may need reminders to persist in their activities and support to create habitual prevention behaviors. From these results, we concluded that creating social norms, supporting discussions among farmers, and using environmental adaptations may result in more preventive behavior.